Supporting Students with Disabilities During Group Activities: Five Tools Every Inclusive Mathematics Educator Needs - Riden, Benjamin S.; Markelz, Andrew M.; Heid, M. Kathleen (Journal of the American Academy of Special Education Professionals, 2018)
The purpose of this research study was to determine how Community Based Instruction (CBI) affects the social skills of middle school students with moderate to severe disabilities. Existing literature is limited in findings related to the influence of CBI on middle school students with moderate to severe disabilities. This qualitative study was completed using interviews and observations. Participants included students, teachers, and paraprofessionals from a middle school in Southern California. The findings of this study are intended to support the use of CBI in middle school special education classrooms and to demonstrate how a functional program can improve the social skills of students with moderate to severe disabilities. Educators and administrators who may want more information on CBI and its benefits may also utilize the findings.